Menelisik Digital Marketing dan Unique Selling Point pada Skincare Indonesia - Fatima Hirawaty; Gede Sri Darma (Universitas Pendidikan Nasional, 2022)
This research to determine the customer’s behavior of Indonesian skincare brand Somethinc towards to digital marketing and unique selling point for Somethinc. The used of qualitative method was applied called purposive sampling as determination of the select informants and the researcher obtained as much as. The data from this study were examined in several strep first the process of data collection, data reduction, explained conclusions and verifying data. Research can provide information to readers interested in digital marketing and unique selling point to identify customer behavior. As a basis for future research on customer behavior and brand image by digital marketing and unique selling point